Software defined radio : digtital tuning front end design and FM IF analog to digital conversion - 236274 Lee, Chun Yoong; Ameruddin Baharom; Fakulti Kejuruteraan Elektrik (2005)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2005